Tightly coupled carbon, nitrogen, and iron utilization by bacteria in the lower photic zone of the North Pacific Subtropical Gyre - Lauren E. Manck; Miranda Herschel Seixas; Rhea K. Foreman; Jingxuan Li; Benedetto Barone; Randelle M. Bundy; Daniel J. Repeta; David M. Karl; Matthew J. Church (Limnology and Oceanography, 2026)
The metabolism of heterotrophic bacteria acts as a key control on the turnover of organic matter in the ocean. However, much remains unknown about how nutrient availability, particularly iron concentration, impacts bacterial growth. In the dimly lit waters of the lower photic and upper mesopelagic zones, the attenuation of sinking particulate flux is intense, due in part to remineralization by heterotrophic bacteria. In the North Pacific Subtropical Gyre, dissolved iron concentrations display a subsurface minimum near the base of the photic zone, and this is also a region where bacteria have elevated cellular iron demands. In a series of field experiments, we examined how the availability of iron, nitrogen, and organic carbon impacts bacterial metabolism in the lower photic zone. Results of these experiments suggest that low iron conditions limit the turnover of organic carbon by bacteria, potentially enhancing the efficiency of organic carbon export to the deep sea. Uptake of both dissolved iron and inorganic nitrogen by heterotrophic bacteria was greatest when bacteria metabolized carbon‐rich organic substrates, typical of the lower photic zone, compared to particulate material collected in the near‐surface ocean. Vertical changes in the composition of organic matter may be an important control on bacterial cellular iron requirements, potentially pushing this community toward iron limitation in the interior waters of the ocean.